THE EFFECT OF YOGASANA ON ATHEROSCLEROSIS HEART DISEASE - Phatak D Shruti (International Journal of Applied Ayurved Research, 2018)
Historical Review: Yoga and Ayurveda have same basic terminology being complemen-tary to each other .Swasthyarakshan and Vyadhiparimoksha both could be achieved through Yoga and it could be one of the powerful ‘Therapeutic Modality ’ ( Chikitsa Upakrama) also . Yogic exercise could be termed as Vihar Chikita .Yoga plays a vital role in normalizing physiology of body and mind . Atherosclerotic Heart Diseases are common pathological conditions in today’s era. Atherosclerosis is characterized by intimal lesions called fibro-fatty plaques that protrude into and obstruct vascular lumen ,weaken it . The narrowing of arteries limits the flow of oxygen-rich blood to parts of the body. Yogopachar is thought to contribute in treating the condition up to certain extent or improving the quality of life parameters in such conditions . Pilot study was conducted to assess the efficacy of Yogopachar in Chronic Ischemic Heart Disease patients due to atherosclerotic changes . Aim: 1) To assess efficacy of Yogopachar in Atherosclerotic Heart Diseases . Objectives: 1) To assess efficacy of Yogopachar for improvement of quality of breathing ( depth, duration). 2) To assess efficacy of Yogopachar for improving psychological health by assessing Quality of Life in terms of positivity of mind , quality of sleep and level of fatigue. Results : 1) Gradual increase in the elasticity of the rib cage and spine . 2) Breathing process became deeper and fuller. 3) Quality of Life improved with gradually increased energy level with more freshness and positive mind .